Answer:
Step-by-step explanation:
(x+1)(x−3)(x−4)
=((x+1)(x−3))(x+−4)
=((x+1)(x−3))(x)+((x+1)(x−3))(−4)
=x3−2x2−3x−4x2+8x+12
=x3−6x2+5x+12
I think that it is 9 because 14-10=4 so 3+2+4=9 I’m not that sure tho let me know if I’m wrong
Answer: 7(1+2x)
Step-by-step explanation:
7 and 14 can be divided by 7. As a result, you take 7 out and bam!
Answer:
negative
Step-by-step explanation:
Answer:
The answer to your question is: 19 l
Step-by-step explanation:
Data
20 quarts to liters
Process
Rule of three
1 quart ------------------ 0.946 l
20 quarts -------------- x
x = (20 x 0.946) / 1
x = 18.92 l ≈ 19 l